Productivity improvement of fish crackers processing using simulation technique - Wan Nurul Afiqah, Wan Mohd Shafie (2013)
Fish cracker is one of the famous foods that originated from East Coast of Malaysia consists of Terengganu, Kelantan and Pahang. It is mainly made from mixing of sago flour, fish, egg, salt and water. Up today, fish crackers are traditionally produces by small industries that not acquire the good practices and latest technology. Therefore, this industry has a lot of inadequacy to expand due to low productivity and unreliable production management. Looking into this issue, the purpose of this study is to determine optimum process layout configuration fish crackers factory using computer simulation analysis. This study adopts industrial engineering concept to help the entrepreneur of fish crackers to increase their productivity. Generally, this layout planning is involving the overall process of fish crackers production. Study started with identification all the process and the types of fish crackers production. Then, process variables such as customer requirement and function of the entire machine are being defined and the time production for all processes is being taken. The process continued with some of the layout being created using WITNESS Software for the all process that involve in the production of fish crackers. Based on the purpose outlined, suggestion and recommendation for improvement has been proposed. Upon completion of this study, it can be applied by the entrepreneurs who seriously involved in the fish crackers manufacturing industry to fulfill the market requirement.